Upregulation of HLA‐E by dengue and not Zika viruses. Issue 9 (25th September 2018) - Drews, Elena; Adam, Awadalkareem; Htoo, Phone; Townsley, Elizabeth; Mathew, Anuja
Abstract: Introduction: The most severe form of dengue virus (DENV) illness, dengue haemorrhagic fever, is characterised by plasma leakage and increased vascular permeability. Objectives: Given the critical role that endothelial cells play in the pathogenesis of DENV, we wanted to determine whether infection with DENV altered the expression of MHC class I related genes including HLA‐E. Results: In this study, we provide evidence that HLA‐E but not MICA/B or HLA‐G is upregulated by all four serotypes of DENV in an endothelial cell line human microvascular endothelial cells (HMEC)‐1. In contrast, Zika virus (ZIKV), a related flavivirus, where plasma leakage is not a major manifestation of disease, did not upregulate HLA‐E. We found modest levels of soluble HLA‐E in supernatants from DENV but not ZIKV‐infected cells. Coculture experiments found minimal activation of natural killer (NK) cells in the presence of both uninfected and infected HMEC‐1 cells. HLA‐E induced by DENV infection could not dampen the degranulation of activated NK cells by interacting with its ligand NKG2a. Conclusions: Our results suggest that while DENV infection induces HLA‐E, the high MHC class I expression on uninfected and infected HMEC‐1 cells may dominate the diverse signals generated between inhibitory and activating receptors on NK cells and ligands on target cells. Abstract : We found that HLA‐E is upregulated on endothelial cells following dengue virus infection. In contrast, Zika virus, a related flavivirus, did not upregulate HLA‐E in the same cell line. Interactions between inhibitory and activating receptors following dengue infection need to be further explored.